Purified Astaxanthin from Haematococcus pluvialis Promotes Tissue Regeneration by Reducing Oxidative Stress and the Secretion of Collagen In Vitro and In Vivo. (4th August 2020) - Chou, Hsin-Yu; Ma, Dik-Lung; Leung, Chung-Hang; Chiu, Chien-Chih; Hour, Tzyh-Chyuan; Wang, Hui-Min David
Abstract : Intracellular reactive apoptosis and reactive oxygen species (ROS) play a crucial role in ultraviolet- (UV-) induced inflammation and aging reaction in human dermal tissues. This study determines the mechanism by which Haematococcus pluvialis extracts (HPE) and purified astaxanthin (HPA) to promote skin regeneration in the injured tissue in vitro and in vivo . The results show that HPE and HPA decrease the DNA damage and promote the secretion of collagen from the human normal fibroblast cell line (Hs68) in a dose-dependent manner. UV irradiation and HPA reduce oxidative stress damage due to phorbol-12-myristate-13-acetate (PMA). When skin cells are injured by free radicals, cells undergo a programmed cellular death. Cellular apoptotic death is determined using annexin V-fluorescein isothiocyanate (FITC)/propidium iodide (PI) double staining to verify that there is no cell membrane asymmetry and that the nuclear membrane is broken. Inflammatory symptoms and apoptotic injuries to experimental rats in a group that is treated with HPA treated are decreased in a dose-dependent manner after UVB exposure (300 mJ/cm 2 ) for 15 min in vivo, compared to the vehicle control group. These positive results show that HPA repairs UVB-triggered skin tissue injury and aging by conducting electrons out of cells to maintain a low level of oxidative stress so that collagen is synthesized in vitro and in vivo .